(untitled) (Biological Sciences - PJSIR, 2000)
In an attempt towards synthesis of intermediates (2a) 2-( l-cyanoethyl) cyclohexanone, (2b), 2-( l-nitroethyl) cyclo- hexanone reaction of morpholinomethyl cyclohexanone hydrochloride with CH)CN (or CH)N02) was undetaken. Instead of the two intermediates namely 2a, 2b the known compound 3 1-(l-oxo-2-hydroxycyclohexyl)-2-(2- oxocyclohexyl)-ethane was obtained. Oxidation of this compound and its LAH reduction product 4 1-(1,2- dihydroxycyclohexyl) -2-(2-hydroxycyclohexyl) ethane with CrO/Ac OH furnished a hitherto un-described com- pound 5, oxa-spiro [5,9] -pentadecane-l,8,13 trione. Its structure was established using spectroscopic techniques such as IR, HRIMS ’H-NMR, IlC-NMR etc. Antibacterial activities of the three synthesized compounds have been evaluated.